Pengembangan E-LKPD Berbasis Model Pembelajaran Group Investigation Berbantuan Liveworksheets pada Pembelajaran IPA - Ramadhan, Ari; Widi Winarni, Endang; Gumono (UNIB Press, 2025)
This study aims to develop and test the feasibility and effectiveness of Electronic Student Worksheets (E-LKPD) based on the Group Investigation (GI) cooperative learning model supported by the Liveworksheets platform in improving the cognitive learning outcomes of fifth-grade students on the properties of light. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results of the study indicate that this E-LKPD has a very high level of validity based on assessments from various experts. Validation by material experts obtained a score of 0.96, linguists 0.92, media design experts 1.00, and item validation 0.99, all of which are included in the very valid category. The effectiveness test showed a significant increase in learning outcomes, with an average N-Gain value of 76.87%, which is included in the effective category. The conclusion of this study is that the E-LKPD based on Group Investigation assisted by Liveworksheets is very valid, effective, and suitable for use as an interactive learning medium in elementary schools. This e-LKPD not only helps students understand material concepts better, but also encourages active involvement in the collaborative learning process.